Peningkatan Hasil Belajar Siswa Melalui Model Problem Based Learning Berbantu Google Meet - Wibowo, Agus (Universitas Sebelas Maret, 2020)
The purpose of this research is to improve student learning outcomes on water’s Cycle material in class V through the application of the Problem Based Learning model with the help of Google Meet. The research conducted was Classroom Action Research (CAR) in two cycles. Each cycle consists of planning, action, observation, and reflection. Data collection techniques used were observation, tests, and documentation of teacher and student activities, as well as written tests of student learning outcomes. In the first cycle of students who completed by 66,7%. In the second cycle of students who completed by 83.3%. These results indicate that the application of the Problem Based Learning model with the help of google meet can improve student learning outcomes on the Water Life Cycle material for fifth grade students at SD Negeri Jeblogan 4 for the 2019/2020 academic year.